Hepatic angiomyolipoma: an international multicenter analysis on diagnosis, management and outcome. Issue 4 (April 2020) - Klompenhouwer, Anne J.; Dwarkasing, Roy S.; Doukas, Michael; Pellegrino, Silvia; Vilgrain, Valerie; Paradis, Valerie; Soubrane, Olivier; Beane, Joal D.; Geller, David A.; Nalesnik, Michael A.; Tripke, Verena; Lang, Hauke; et al.
Abstract: Background: Hepatic angiomyolipoma (HAML) may easily be misdiagnosed as a malignancy. The study aim was to assess diagnostic dilemmas, clinical management and outcome of this rare tumor. Methods: This retrospective international multicenter study included all patients with pathologically proven HAML diagnosed between 1997 and 2017. Data on patient characteristics, diagnostic work-up, management and follow-up were analyzed. Results: Thirty-eight patients were included, 32 female. Median age was 56yrs (i.q.r. 43–64) and median HAML-diameter was 57.5 mm (i.q.r. 38.5–95.3). Thirty patients had undergone CT and 27/38 MRI of the liver, diagnostic biopsy was performed in 19/38. Initial diagnosis was incorrect in 15/38 patients, of which 13 were thought to have malignancy. In 84% biopsy resulted in a correct preoperative diagnosis. Twenty-nine patients were managed with surgical resection, 4/38 with surveillance and 3/38 with liver transplantation. Recurrence after resection occurred in two cases. No HAML related deaths or progression to malignancy were documented. Conclusion: HAML diagnosis proved problematic even in hepatobiliary expertise centers. Biopsy is indicated and may provide valuable additional information when HAML diagnosis is considered on cross-sectional imaging, especially when surgical resection imposes a risk of complications. Conservative management with regular imaging follow-up might be justified when biopsy confirms (classic type) HAML.